A clinical review: schizophrenia, transsexualism or their combination? - V. A. Soldatkin (Медицинский вестник Юга России, 2022)
The change in the position of transsexualism in the new ICD classification, the hot debate about the psychopathological structure of this phenomenon and its relation to other mental disorders determine the relevance of considering the following clinical case.A detailed clinical description demonstrates the possibility of combining two initially independent disorders - transsexualism and schizophrenia - which gave a bright individual color to the clinical picture and caused difficulties both in the medical and legal aspects of patient care.At the age of 25, a patient with clinical signs of transsexualism developed acute paraphrenia psychosis. Without medical assistance, according to the mechanisms of sanogenesis, the severity of the condition decreased, but the psychotic state was not recovered. Features of the onset and dynamics of psychosis typical for the continuous type of paranoid schizophrenia (acuteness of development and absence of signs of syndromotaxis) allow us to attribute it to episodic with progressive or stable deficit paranoid schizophrenia variant. It is noteworthy that after the onset of psychosis, the stereotype of the development of birth-assigned gender rejection syndrome did not undergo significant changes: the formation of crossdressing, inverse psychosexual identity and inverse gender identity were finally completed; mimicry reactions became bright, self-destructive tendencies began to appear more and more clearly, and the patient applied for permission to change gender.In the described clinical situation, the primary task is to overcome the acute schizophrenia psychosis. After solving this problem, the secondary prevention and rehabilitation program development becomes more important. Formally, the patient does not have the right to change sex, since she suffers from schizophrenia, which is a contraindication for sex transformation. In the state of psychosis, the patient essentially loses her civil procedural capacity. Informally, the question remains relevant.